SOVEREIGN RIGHT CLAIM ON GEO STATIONARY ORBIT (GSO) - Arafah, Adhy Riadhy (UI Scholars Hub, 2012)
The potency and unique characteristics of GSO for placing communication satellites located only above equatorial states makes the GSO as part of natural resources. The equatorial states realized that the use of GSO has many advantages and has implications to their national interest. However, basic principle in space law, Outer Space Treaty 1967 (Art.II), states that equatorial states forbidden to claim ownership of any part of outer space, particularly claim in sovereignty. The principle “first come first served” in placing of satellite on GSO, practically only gives the advantage to developed countries which have high satellite technology. Hence, the level of technology of a state plays important role in developing of space law internationally. The equatorial states which are mostly developing states (low and middle level in technology in outer space activities) claimed their right to use natural resources for their national interest based on equatorial position principle